The Relationship Between Psychological Capital and Entrepreneurial Traits: A Case Study of MBA SBM ITB Students in Bandung - Al Rasyid, Adipraja; Bangun, Yuni Ros (Journal of Business and Management, 2015)
Abstract-Psychological Capital or Psycap is a concept developed by Luthans and his colleagues in which theorized the role of one’s positive psychological disposition could add competitive advantage to organizations and individuals alike, much like Social and Financial Capital could. The Psycap concept is composed of specifically the four positive psychological capacity of hope, self-efficacy, optimism, and resiliency. Given the lack of research regarding the relationship of Positive Psychological Capital with entrepreneurial traits, this research aims to find it. As a business school that emphasizes heavily on entrepreneurial vision for their students, the research uses MBA Students of School of Business and Management ITB as a sample of the study and uses descriptive statistics along with SEM analysis to analyze the hypothesized relationship of positivity and entrepreneurship.The result conclusively proves, that Psycap positively affects entrepreneurial traits of the students, with optimism and resiliency to be the state with the highest impact on entrepreneurship. Keywords:Psychological Capital, Entrepreneurial Trait, Positivity,Entrepreneurship, Bandung